HR Competence and Internal Control System on the Quality of Financial Statements at PT. SPIL - Nikmah, Anisa; Pandin, Maria (Indonesian Journal Publisher, 2026)
This study examines the impact of PT Salam Pacific Indonesia Lines' internal control system and employee capabilities about the caliber of financial reporting. In this study, questionnaires were distributed to 235 employees to collect primary data, and saturation sampling was used to cover all participants. The data was evaluated by applying multiple regression analysis. The findings show that the internal control system shows that the quality of financial reporting is not much impacted by staff competencies. The quality of financial reporting is also greatly influenced by the personnel's skills and the internal control system. These findings indicate that while an excellent internal control system plays a crucial role in providing high-quality financial reporting, the capabilities of personnel also play a significant role when supported by strong control mechanisms.